2020
DOI: 10.21203/rs.3.rs-31615/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous Endometrial Volumetric Analysis for Endometrial Receptivity Assessment on Assisted Reproductive Technology Cycles

Abstract: Research Question: Human implantation is a complex process requiring synchrony between a healthy embryo and a functionally competent or receptive endometrium. In order to assess endometrial receptivity in Assisted Reproductive Technology (ART) cycles continuous evaluation of endometrial volumetric analysis may have a predictive value on a positive outcome.Design: Serial 3D transvaginal ultrasound performed in women on ART cycle to evaluate a pattern that better predicts implantation rates. 169 subjects on a pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Our results showed that endometrial volume differed between the two groups in the univariate analysis but not in the multivariate analysis, suggesting that the endometrial volume was not an independent predictor of pregnancy. Our study showed that endometrial morphology was not a factor associated with pregnancy occurrence (P > 0.05), consistent with the results of Martins et al [3]. Uterine artery parameters (mPI, mRI, and mSD) were not significantly correlated with pregnancy occurrence (P > 0.05), which might be because the uterine artery supplies several vital structures, such as fallopian tubes and ovaries, in addition to the uterus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that endometrial volume differed between the two groups in the univariate analysis but not in the multivariate analysis, suggesting that the endometrial volume was not an independent predictor of pregnancy. Our study showed that endometrial morphology was not a factor associated with pregnancy occurrence (P > 0.05), consistent with the results of Martins et al [3]. Uterine artery parameters (mPI, mRI, and mSD) were not significantly correlated with pregnancy occurrence (P > 0.05), which might be because the uterine artery supplies several vital structures, such as fallopian tubes and ovaries, in addition to the uterus.…”
Section: Discussionsupporting
confidence: 91%
“…The success of an IVF-ET depends on certain factors, including endometrial receptivity. Endometrial receptivity refers to the window of implantation (WOI) during which the uterus allows embryo implantation to occur [2] and is considered one of the most important factors [3]. A satisfactory endometrial receptivity refers to the state in which the endometrium allows the embryo to adhere, with subsequent corresponding endometrial changes for the implantation [4].…”
Section: Introductionmentioning
confidence: 99%